(untitled) (Journal of Hama University, 2021)
Foliar and soil fertilization with EM1 bio-fertilizer at two concentrations (3, 4 ml/l) were used in three stages (before leave fall, before flowering, a month before harvesting), while the control was left without fertilization, and its effect on some qualitative and vegetative characteristics of the Coscia pear trees was studied during the 2020 season. The results showed that foliar fertilization with EM1 at concentration (4 ml /l) was superior in significant differences in the percentage of total soluble solids (T.S.S), chlorophyll A, B and total (A + B) (13.6%, 1.24 mg / g, 0.84 mg/g, 2.08 mg/g) respectively, compared with the control (12.47%, 0.71 mg/g, 0.44 mg/g, 1.15 mg/g), respectively. In addition, soil fertilization with EM1 at concentration (4 ml/l) improved significantly the percentage of total sugars (%), and fruit pH (12.75 %, 4.63) respectively, while the control treatment was (5.87%, 4.21). However Soil fertilization with EM1 at concentration (3 ml/l) increased vitamin C in the fruits (14.73 mg /100 g fresh weight) compared with the control (11.33 mg / 100 g fresh weight).